2015
DOI: 10.1021/acs.langmuir.5b00127
|View full text |Cite
|
Sign up to set email alerts
|

An NH Moiety Is Not Required for Anion Binding to Amides in Aqueous Solution

Abstract: Herein, we use a combination of thermodynamic and spectroscopic measurements to investigate the interactions of Hofmeister anions with a thermoresponsive polymer, poly(N,N-diethylacrylamide) (PDEA). This amide-based polymer does not contain an NH moiety in its chemical structure and, thus, can serve as a model to test if anions bind to amides in the absence of an NH site. The lower critical solution temperature (LCST) of PDEA was measured as a function of the concentration for 11 sodium salts in aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 43 publications
(79 reference statements)
9
84
0
5
Order By: Relevance
“…On the other hand, the anions to the right of chloride (Cl -) are called chaotropes, which are weakly hydrated and may increase the LCST of polyacrylamides. The similar influence is not only discovered in N-alkyl-substituted polyacrylamides based on the secondary amide or tertiary amide, such as PNIPAM and PDEAM, 49,57 but also has also been verified in another thermoresponsive polymer of elastin-like polypeptides. 58 The study of the interaction between Hofmeister ions and thermoresponsive polymers, including the analysis methods and the binding mechanism, are helpful to tune the thermoresponse behavior.…”
Section: Salt Effect On the Phase Transition Of Pnasmesupporting
confidence: 58%
“…On the other hand, the anions to the right of chloride (Cl -) are called chaotropes, which are weakly hydrated and may increase the LCST of polyacrylamides. The similar influence is not only discovered in N-alkyl-substituted polyacrylamides based on the secondary amide or tertiary amide, such as PNIPAM and PDEAM, 49,57 but also has also been verified in another thermoresponsive polymer of elastin-like polypeptides. 58 The study of the interaction between Hofmeister ions and thermoresponsive polymers, including the analysis methods and the binding mechanism, are helpful to tune the thermoresponse behavior.…”
Section: Salt Effect On the Phase Transition Of Pnasmesupporting
confidence: 58%
“…Analysis of the concentration/LCST curves revealed a component of direct anion binding was responsible for the improved solubility, which was presumed to be occurring through the amide group as a hydrogen‐bond donor. The structural basis for salting‐in was analyzed in more detail using PDEA, an LCST polymer with a tertiary rather than secondary amide, and hence no apparent anion‐binding site 91. Combined NMR and IR spectroscopic studies showed that the same chaotropic anions were interacting with the α‐CH proton on the polymer backbone.…”
Section: Macromolecular Recognition Of Anions In Watermentioning
confidence: 99%
“…[11]) in Gleichung (3) Die stärkere Wechselwirkung von Kationen mit der C=O-Gruppe von NMA gegenüber der Wechselwirkung der Anionen mit der N-H-Gruppe stimmt auch mit Ergebnissen von Moleküldynamiksimulationen überein. [11]) in Gleichung (3) Die stärkere Wechselwirkung von Kationen mit der C=O-Gruppe von NMA gegenüber der Wechselwirkung der Anionen mit der N-H-Gruppe stimmt auch mit Ergebnissen von Moleküldynamiksimulationen überein.…”
Section: Angewandte Chemieunclassified
“…B. das Amidgrundgerüst, die Aminosäure-Seitenketten oder die Te rmini eines Proteins) aufweisen. [9,[11][12][13][14] Direkte Wechselwirkungen werden manchmal infrage gestellt, [15] allerdings zeigen NMR-Untersuchungen, dass die chemische Verschiebung der Protonen der Amidgruppe durch Anionen beeinflusst wird [9,11,12] und dass der Abstand von Anionen zur Amidgruppe der Hofmeister-Reihe folgt. [3] Direkte Wechselwirkungen zwischen Ionen und dem Amidgrundgerüst, dem grundlegenden Strukturmerkmal aller Proteine,w urden mit verschiedensten spektroskopi-schen Methoden untersucht.…”
unclassified
See 1 more Smart Citation